The Effect of Extract Supplements of Moringa Oleifera Leaves Plus Royal Jelly on Hemoglobin (Hb) Levels of Anemia Pregnant Mother in Takalar Regency - Yulni, Yulni; Hadju, Veni; Bahar, Burhanuddin; Citrakesumasari, Citrakesumasari; Indriasari, Rahayu; Zainal, Zainal (International Journal Papier Advance and Scientific Review, 2020)
The aim of this study was to determine the effect of Moringa oleifera leaf extract supplements, Moringa oleifera leaf extract plus royal jelly and placebo on hemoglobin levels in anemic pregnant women. This research is a randomized controlled double blind design study which was conducted in Polombangkeng Utara District, Takalar Regency for 2 months. The subjects of this study were pregnant women with anemia, the majority of which were 20-35 years old, primigravida parity, income less than UMR, unemployment, higher education, pregnancy distance of more than 2 years with p value> 0.05. Then divided into three groups, namely Moringa capsules plus royal jelly (KRJ) (n = 24), Moringa capsules (KTR) (n = 24) and placeco (PLC) (n = 21). Before and after the intervention, measurements of hemoglobin levels were carried out using the Hemocue tool and interviewing the characteristics of the respondents. The results showed that the average Hb level increased from each group (mean SD): KRJ 10.06 ± 0.75 to 11.42 ± 1.23, P = 0.001, KTR 10.40 ± 0.46 to 11.15 ± 0 , 90 P = 0.001 and PLC 10.43 ± 0.42 becomes 11.14 ± 0.88 P = 0.002. but there was no significant difference from the difference in the average increase in Hb levels in the three groups, but there was a tendency that KRJ was superior to the KTR and PLC groups with an increase of 1.36 gr / dl, KTR 0.75 gr / dl and PLC 0.71 gr / dl. So it can be concluded that KRJ is better than KTR and PLC in increasing Hb levels in anemic pregnant women in Takalar Regency.